A critical review of the literature regarding physical therapy management of patients with total knee arthroplasty. Issue 6 (November 2015) - Unknown
Abstract : This review analyzes the research literature on physical therapy management of patients anticipating or recovering from total knee arthroplasty (TKA). Using databases and keywords, several relevant studies were found. Twenty-four studies met the criteria and were classified according to Sackett's levels of evidence. Fifteen studies were graded as level I, five studies as level II, one as level IV, and three as level V. From the levels of evidence, seven grade A, four grade B, and one grade C recommendations were developed, with grade A being the most significant. The results of this review found that there is a potential benefit to using accelerated procedures (initiation of rehabilitation within 24 hr after TKA). Encouraging patients to perform active range of motion exercise would be a better option than passive range of motion and that physiotherapy can focus on more functional rehabilitation, such as preparing to return to daily activities. Eccentric exercise of the hamstring is one of the effective methods to recover knee extension after TKA. A multidisciplinary rehabilitation program, including a physician specializing in physical medicine and rehabilitation, a physical therapist, a psychologist, a social worker, a nutritionist, and an orthopaedic surgeon in the outpatient setting, does not reduce the use of rehabilitation services or yield faster achievement of functional recovery or quality of life. Functional training and balance training are safe treatment methods and have the potential to decrease functional limitations. Clinical recommendations and future research directions also are provided.